The Value of determination : the story of Helen Keller - Johnson, Ann Donegan (La Jolla, CA : Value Comm, 1976)
Focuses on Helen Keller's determination to help, hear, see, and speak and her equal determination to help others with handicaps similar to her own.
Keywords: Keller, Helen Adams, 1880-1968; Blind-deaf; Perseverance (Ethics); Physically handicapped